Improving Mobile Robot Navigation Using Deep Q-Learning with Diagonal Motion under Dynamic Obstacle Environments - Karam A Al-Zubaidi; Ahmed M Alkamachi; Bahaa Ansaf (Universitas Ahmad Dahlan, 2026)
Navigation of the mobile robot in dynamic environments is a significant challenge for researchers due to the uncertainty and rapid changes in obstacle movement. This study proposes a framework for navigating a mobile robot using a deep Q-learning (DQL) algorithm in environments containing both static and dynamic obstacles. The research contribution lies in integrating diagonal motion to enhance manoeuvrability and improve decision-making under dynamic conditions. This paper compares the model with the basic motions model (front, back, right, left). The comparison is conducted across four environments of varying difficulty in terms of the density of obstacles. The model is trained by 3000 episodes using a Deep Q-Network (DQN) with two fully connected hidden layers consisting of 128 and 64 neurons, respectively, employing a greedy policy and utilizes a LiDAR simulator for spatial perception. Both models achieved a 100% success rate in reaching the target without collision in environments A and B, and 90% in environments C and D. However, the proposed approach succeeded in reducing the average number of steps required to reach the goal in all four environments, shortening the path by 10% to 20%. This reduces the time and energy required to reach the goal, which is a significant and crucial advantage in real-world environments. Even when tested at obstacle speeds up to six times the robot's speed, it demonstrated superiority compared to the other model. The model showed very good performance even with noise on the LiDAR reading. In short, the proposed model offers a robust and scalable approach to mobile robot navigation in real-world environments.